Mapping the human alpha globin gene complex to 16p13.2----pter. Issue 12 (December 1987) - Simmers, R N; Mulley, J C; Hyland, V J; Callen, D F; Sutherland, G R
Abstract : The regional localisation of the alpha globin (HBA) complex on the short arm of chromosome 16 was investigated by in situ hybridisation, Southern blot analysis, and linkage analysis using the fragile site at 16p12.3 (FRA16A) and translocation breakpoints within band 16p13.1. HBA was found to be distal to the two translocation breakpoints within band 16p13.1 and not closely linked to FRA16A. In situ hybridisation to the distal portion of the fragment on metaphase chromosomes expressing the fragile site and the observation of considerable recombination between FRA16A and HBA supports a localisation for HBA closer to the telomere than to FRA16A, at 16p13.2----pter.